Evaluation of the Efficacy of Disinfectant Footmats for the Reduction of Bacterial Contamination on Footwear in a Large Animal Veterinary Hospital. (12th October 2016) - Hornig, K.J.; Burgess, B.A.; Saklou, N.T.; Johnson, V.; Malmlov, A.; Van Metre, D.C.; Morley, P.S.; Byers, S.R.
Abstract : Background: Infection control is critical to providing high‐quality patient care. Many veterinary teaching hospitals (VTHs) utilize footbaths or footmats at entrances and key control points throughout the facility to decrease trafficking of pathogenic microorganism on contaminated footwear. Hypothesis/Objectives: To compare efficacy of 4 disinfectants used in footmats for decreasing bacterial contamination of footwear in a large animal hospital. Animals: A single adult dairy cow was housed in a stall for 4 days to facilitate stall contamination with fecal material. Methods: Overboots were experimentally contaminated with organic material in a standardized manner. Each boot was randomly assigned to 1 of 5 treatments (no treatment, or exposure to 1 of 4 disinfectants: an accelerated peroxygen [AHP], a peroxygen [VIRKON], a quaternary ammonium [QUAT], and a phenolic disinfectant [PHENOLIC]) by stepping on a soaked footmat and collecting samples from boot soles. Generalized linear modeling was used to analyze differences in bacterial counts. Results: Reductions in colony‐forming units (CFUs) on treated boots ranged from no detectable reduction to 0.45 log10 and varied by disinfectant. Percentage reductions in total bacterial counts generally were larger (albeit still modest) for AHP and QUAT disinfectants (range 37–45%) and smallest for the PHENOLIC (no detectable reduction). Conclusions and Clinical Importance: In general, use of disinfectant footmats was associated with significant reductions in viable bacteria on overboots—albeit with variable efficacy. Footmats may be useful adjuncts to cleaning and disinfection programs for decreasing trafficking of microorganisms throughout VTHs but should not be considered as a sole prevention method.